The Use of Learning Management System and Its Effect on Learning Effectiveness at State Islamic University - Anwar, Rosihon; Muhyi, Asep Abdul; Rudianto, Apip (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2024)
As a result of the research, the data regarding the application of e-learning based on the Learning Management System (LMS) at UIN SGD Bandung is a form of readiness to welcome the digitization of education, which started in 2020. The university formed an exceptional IT team called PTIPD to handle the digitization of education by applying e-learning based on the Learning Management System (LMS). This research uses a qualitative method. From the results of interviews with several lecturers at the State Islamic University Sunan Gunung Djati Bandung regarding the use of e-learning based on the Learning Management System (LMS), the most widely used applications are e-knows and Google Classroom applications, there are also other applications such as zoom applications, google meet, WhatsApp, and others. The effectiveness of LMS at UIN SGD Bandung on learning depends on how the method is applied and how well students and teachers can adapt to technology in the learning context. Based on the description above, several factors influence learning using the LMS Learning Management System to be ineffective: lack of integration between online and face-to-face components, limitations in the use of technology, restrictions on interaction in learning, poor class management, and poor teaching quality.